Analisis Kebutuhan Air Bersih Pada Dusun Mamunu Desa Lingadan Kecamatan Dakopemean Kabupaten Tolitoli - Melda (Formosa Journal of Sustainable Research, 2022)
The state guarantees the right of everyone to get water for their daily minimum basic needs in order to fulfill a healthy, clean, and productive life. This means that access to clean water is the right of citizens and the responsibility of the state to provide it. Given that not all areas get clean water, it is necessary to have an even distribution of clean water for the community as is the case in one of the residential areas in Tolitoli Regency, especially in Mamunu Hamlet, Lingadan village, which has received clean water services but has not been optimally distributed. This study aims to determine the clean water needs of the Momunu village community in 2022 and for the next 5 (five) years. The development of the population as users of clean water was analyzed using a geometric method approach. Based on the results of data analysis and observations in this study, it can be concluded that the need for clean water in Momunu hamlet can still be fulfilled within the next 5 (five) years. The results of the analysis carried out using the geometric method show that the population of Momunu hamlet for the next five years until 2025 is 506 people with a daily need of clean water of 30,360 liters/day.